2009
DOI: 10.1038/ng.334
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 haplotype is a major risk factor for the development of myeloproliferative neoplasms

Abstract: Chronic myeloproliferative neoplasms (MPNs) are a group of related conditions characterized by the overproduction of cells from one or more myeloid lineages. More than 95% of cases of polycythemia vera, and roughly half of essential thrombocythemia and primary myelofibrosis acquire a unique somatic 1849G>T JAK2 mutation (encoding V617F) that is believed to be a critical driver of excess proliferation1–4. We report here that JAK2V617F-associated disease is strongly associated with a specific constitutional JAK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

33
325
5
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(372 citation statements)
references
References 22 publications
33
325
5
6
Order By: Relevance
“…[2][3][4][5] We confirmed these observations in two recent papers 6,7 and also showed increased JAK2 46/1 haplotype frequency in VF-negative essential thrombocythemia (ET) 6 and primary myelofibrosis (PMF). 7 In the latter two studies, the JAK2 46/1 haplotype frequencies in both PMF (44%) and ET (41%) were significantly higher than that of the Wellcome Trust Case Control Consortium (WTCCC) (24%) or local (28%) control population, but similar in VF-positive versus VF-negative PMF (37 versus 36%) or ET (41 versus 38%), after adjusting for VF allele burden (that is, considering only patients with low allele burden to minimize allelic distortion from acquired uniparental disomy).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…[2][3][4][5] We confirmed these observations in two recent papers 6,7 and also showed increased JAK2 46/1 haplotype frequency in VF-negative essential thrombocythemia (ET) 6 and primary myelofibrosis (PMF). 7 In the latter two studies, the JAK2 46/1 haplotype frequencies in both PMF (44%) and ET (41%) were significantly higher than that of the Wellcome Trust Case Control Consortium (WTCCC) (24%) or local (28%) control population, but similar in VF-positive versus VF-negative PMF (37 versus 36%) or ET (41 versus 38%), after adjusting for VF allele burden (that is, considering only patients with low allele burden to minimize allelic distortion from acquired uniparental disomy).…”
supporting
confidence: 84%
“…JAK2 46/1 haplotype allele frequencies in the study population were compared with those of population (WTCCC; n ¼ 1500) and local (n ¼ 57) controls. 2 For the current study, MPL mutation analysis was performed in 161 consecutive VF-negative patients (median age 55 years; 82 females) with ET (n ¼ 108) or PMF (n ¼ 53). Of these, 12 (B8%) displayed either MPLW515L or MPLW515K, including 6 (6%) of the 108 patients with ET and 6 (B11%) of the 53 patients with PMF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Subsequent studies also showed significant association of this haplotype, with JAK2 exon 12-mutated, 12 JAK2-wild type ET, 13 and MPLW515-mutated PMF or ET, 14 suggesting that this haplotype increases the risk of developing a MPN, regardless of the acquisition of the V617F mutation. However, in another recent study, no such association with MPL mutations was described.…”
mentioning
confidence: 93%
“…The JAK2 (V617F) mutation, found in about two thirds of patients with a myeloproliferative neoplasm (MPN), is preferentially detected in subjects with a common constitutional JAK2 haplotype known as 46/1 or GGCC [1][2][3]. The mechanism underlying this predisposition has not been elucidated so far.…”
mentioning
confidence: 99%